ADDRESSING CHALLENGES IN LANGUAGE TEACHING IN INDIA: EXPLORING THE ROLE OF CORRECTIVE FEEDBACK IN ENHANCING LEARNING - Amrendra Singh; Huzaina Binti Abdul Halim (Novìtnâ Osvìta)
Corrective feedback is a crucial aspect of language teaching, which aims to help students improve language accuracy and fluency. While research on corrective feedback has been conducted worldwide, there is a dearth of empirical studies in the Indian context. Despite this gap, several studies suggest that corrective feedback practices in India are based mainly on traditional grammar-translation methods prioritizing accuracy over fluency rather than considering students' needs and learning styles. Issues related to corrective feedback in India include cultural factors, optimal timing, teacher beliefs, technology-mediated feedback, and student motivation. Cultural factors such as societal expectations and values can influence teachers' and learners’ attitudes toward corrective feedback. The optimal timing of providing corrective feedback in ESL writing is also an issue, as the effectiveness of immediate versus delayed feedback on language accuracy and fluency is still unclear. Moreover, teachers' views on corrective feedback may influence their practices and need further exploration in the Indian context. The potential of technology-mediated corrective feedback and its effects on student motivation and self-efficacy also require further research (Doley, 2023). Overall, this review highlights the need for more empirical research on corrective feedback practices in India to inform effective teaching practices and enhance the effectiveness of ELT in the country. Future studies should focus on examining cultural factors that influence corrective feedback practices, identifying optimal timing for feedback, examining teachers' views and practices, examining technology-mediated feedback, and examining the effects of corrective feedback on student motivation and self-efficacy.